Food waste and generation management of selected barangays in Quezon City a case study - Caballero, Niña Marie
There are limited studies on the food waste generation and its management in urban cities in Philippines since it is assumed that as a developing country most of its food waste, especially that can be avoided, mostly occurred at the upper stages of food supply chain. In line with this, this paper aimed to measure the proportion of household with avoidable food waste and the average generation of avoidable food waste in selected barangay/s in Quezon City as well as its management at the barangay level.